Integrated care model and point of care diagnostics facilitate Hepatitis C treatment among patients receiving opioid agonist therapy: a retrospective review of medical records - Margareeta Häkkinen; Jouni Tourunen; Tuuli Pitkänen; Kaarlo Simojoki; Sauli Vuoti (BMC, 2022)
Abstract Background Hepatitis C virus (HCV) is common among individuals in opioid agonist therapy (OAT). HCV treatment has previously been unavailable for most HCV positive OAT patients in Finland. The removal of treatment restrictions and attempts to reach HCV elimination goals have increased the number of OAT patients needing HCV treatment. The objectives of this study were 1) to characterize Finnish HCV positive OAT patients and evaluate their eligibility for HCV treatment at addiction service units, and 2) to retrospectively review the outcomes of treated patients. Methods The study focused on HCV positive OAT patients (n = 235). Demographics and clinical parameters were retrospectively reviewed using the patients' medical records. The eligibility of providing HCV treatment to patients at addiction service units were evaluated based on patients' clinical characteristics, such as liver function and patterns of substance use. The outcomes of patients receiving HCV treatment were reviewed. Results Of HCV antibody positive OAT patients, 75% had chronic HCV. Of 103 HCV patients screened for liver fibrosis either with Fibroscan or APRI (aspartate aminotransferase to platelet ratio index), 83 patients (81%) had no indication of severe liver damage. Point of care (POC) HCV tests were used for 46 patients to lower the threshold of attending laboratory testing. All patients preferred POC testing to conventional blood testing. Twenty patients had received HCV treatment, 19 completed the treatment and achieved sustained virologic response (SVR) at the end of the treatment. Of the 18 patients available for evaluation of SVR at 12 weeks after the treatment (SVR12), 17 achieved SVR12. Conclusions The integrated model consisting of HCV diagnostics and treatment at the addiction service unit was successfully implemented within normal OAT practice.